Differentials in happiness among the young old, the middle old and the very old in Thailand - Rungthong Kramanon (2017)
This study investigates factors affecting happiness among the young old, the middle old and the very old in Thailand. The sample includes 4,036 people ages 60 and older who are Buddhists and have at least one living child in the demographic surveillance site in Kanchanaburi, Thailand. Face-to-face interviews were conducted from September to December 2011. Older people were classified into young old (60-64), middle old (65-74) and very old (75 and older). Multiple regression was used to analyze these three age categories separately. Results show three factors that significantly contribute to elder happiness in all age categories: perceived trust in family care, the number of people with whom it is pleasant to talk and perceived health. Economic factors were important for the young old and the middle old. Giving help to children/grandchildren and engaging in religious activities were important only among the very old. Policies should promote health, work opportunities for older adults and religious activities, as well as family, friend and community relationships. It is strongly recommended that such policies be implemented before people reach old age.